How Relevant is Game Theory to Intelligent Agent Technology? - Shoham, Professor Yoav (Proceedings of the IEEE/WIC/ACM International Conference on Web Intelligence, 2007)
At this point, restricted to rather specialized areas, and even there must be taken with a grain of salt. But at the same time you can't afford not to know it; there is currently no better underpinning for understanding multiagent systems. I will elaborate using experience in both academia and industry.